Distinct Immune Profiles of Exhausted Effector and Memory CD8+ T Cells in Individuals With Filarial Lymphedema - Horn, Sacha; Borrero-Wolff, Dennis; Ritter, Manuel; Arndts, Kathrin; Wiszniewsky, Anna; Debrah, Linda Batsa; Debrah, Alexander Y.; Osei-Mensah, Jubin; Chachage, Mkunde; Hoerauf, Achim; Kroidl, Inge; Layland, Laura E. (Frontiers in Cellular and Infection Microbiology, 2021)
CD8+ T cells are crucial for the clearance of viral infections and current research begins to highlight their importance in parasitic diseases too. In-depth research about characteristics of CD8+ T cell subsets and exhaustion remain uncertain, especially during filariasis; a chronic helminth infection. Lymphatic filariasis, elicited by Wuchereria bancrofti, remains a serious health problem in endemic areas in Ghana, especially in those suffering from morbidity due to lymphedema (LE). In this observational study, the characteristics and profiles of CD8+ T cells were compared between asymptomatic Wuchereria bancrofti-infected individuals, uninfected endemic normals and those with LE (grades 2-6). Focusing on exhausted memory (CD8+exmem: CD8+ T-betdimEomeshi) and effector (CD8+exeff: CD8+T-bethiEomesdim) CD8+ T cell subsets, advanced flow cytometry revealed that LE individuals presented reduced frequencies of IFN-+CD8+exmem T cells expressing Tim-3 or LAG-3 which negatively correlated to the presence of lymphedema. Moreover, the LE cohort further showed significantly higher frequencies of IL-10+CD8+exeff T cells expressing either Tim-3, LAG-3, CD39, KLRG-1 or PD-1; all associated markers of exhaustion and that these frequencies positively correlated with the presence of lymphedema. In summary, this study shows that distinct exhausted CD8+ T cell subsets are prominent in individuals suffering from LE, suggesting that enhanced inflammation and constant immune activation might drive exhaustion of CD8+ T cells. Since T cell exhaustion is known to be associated with insufficient control of persisting antigen, the data presented here reveals that these CD8+ T cell exhaustion patterns in filarial lymphedema should be taken into consideration for prevention and control management of lymphedema.